2018
DOI: 10.1038/s41372-018-0189-5
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal Resuscitation and Adaptation Score vs Apgar: newborn assessment and predictive ability

Abstract: NRAS correlates with Apgar status assessment, and identifies newborns who die or may require further care better than the Apgar score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 21 publications
9
18
0
Order By: Relevance
“…In our study, there was a significant moderate positive correlation between Apgar and NRAS scores at 1st min (p=0.001) and a significant strong positive correlation between Apgar and NRAS scores at 5 th min (p=0.001). This comes in agreement with a study was done by Witcher et al, [5] on 340 newborns that detect strong correlation between the two scores. This implies that the ability of NRAS to assess the status of the infant during resuscitation is similar to that of the Apgar score.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, there was a significant moderate positive correlation between Apgar and NRAS scores at 1st min (p=0.001) and a significant strong positive correlation between Apgar and NRAS scores at 5 th min (p=0.001). This comes in agreement with a study was done by Witcher et al, [5] on 340 newborns that detect strong correlation between the two scores. This implies that the ability of NRAS to assess the status of the infant during resuscitation is similar to that of the Apgar score.…”
Section: Discussionsupporting
confidence: 93%
“…Also, this is in agreement with a study done by Li et al, [8] who found that, preterm births had about 10 to 20-time higher incidence of low Apgar score at 5 minutes (<7) than term and post-term births. Also, this is in agreement with a study done by Witcher et al, [5] who showed that NRAS at 1 min was related to gestational age (p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations